Trends in cardiovascular mortality of cancer patients in the US over two decades 1999‐2019. Issue 11 (20th September 2021) - Kobo, Ofer; Khattak, Sophia; Lopez‐Mattei, Juan; Van Spall, Harriette G. C.; Graham, Michelle; Cheng, Richard K.; Osman, Mohammed; Sun, Louise; Ullah, Waqas; Fischman, David L.; Roguin, Ariel; Mohamed, Mohamed O.; et al.
Abstract: Background: Cancer is the second most common cause of death globally after cardiovascular disease, and cancer patients are at an increased risk of CV death. This recognition has led to publication of cardio‐oncological guidelines and to the widespread adoption of dedicated cardio‐oncology services in many institutes. However, it is unclear whether there has been a change in the incidence of CV death in cancer patients. Methods and Results: Using Centers for Disease Control and Prevention Wide‐Ranging, Online Data for Epidemiologic Research (CDC WONDER) Multiple Cause of Death dataset, we determined national trends in age‐standardised mortality rates attributed to cardiovascular diseases in patients with and without cancer, from 1999 to 2019, stratified by cancer type, age, gender, race, and place of residence (state and urbanisation status). Among more than 17.8 million cardiovascular deaths in the United States, 13.6% were patients with a concomitant cancer diagnosis. During the study period, among patients with cancer, the age‐adjusted mortality rate dropped by 52% (vs 38% in patients with no cancer). In cancer patients, age‐adjusted mortality rate dropped more significantly among patients with gastrointestinal, breast, and prostate malignancy than among patients with haematological malignancy (59%‐63% vs. 41%). Similar reduction was observed in both genders (53%‐54%), but more prominent reduction was observed in older patients and in those living in metro areas. Conclusions: Our findings emphasise the role of multidisciplinary management of cancer patients. Widespread adoption of cardio oncology services have the potential to impact the inherent risk of increased CV mortality in both cancer patients and survivors.